2017
DOI: 10.4103/ortho.ijortho_212_16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of an Initial 3-month Trial of Conservative Treatment for Femoroacetabular Impingement

Abstract: Background:Femoroacetabular impingement (FAI) can be managed either conservatively or by a surgical correction of the deformity causing impingement. However, there is insufficient evidence to justify an immediate surgical treatment in all symptomatic patients, and the role of a nonoperative treatment is unclear. This study evaluates the role of conservative treatment for FAI.Materials and Methods:87 patients (102 hips) diagnosed as FAI between January 2011 and May 2012 were included in this retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Surgical treatment is indicated in cases when conservative treatment brings only temporary relief. [ 6 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment is indicated in cases when conservative treatment brings only temporary relief. [ 6 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Of the 5 included studies, [ 4 , 7 , 9 , 10 , 25 ] 3 studies [ 4 , 7 , 9 ] were RCTs, one [ 10 ] was a prospective cohort study, and the other one [ 25 ] was a retrospective cohort study. A total of 838 patients were included in the studies selected: 382 patients underwent arthroscopic treatment, and 456 patients were treated by nonsurgical intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The mean ages among the study samples ranged from 15.3 to 45.1 years, and the mean follow-up durations ranged from 8 to 26.8 months. Three [ 9 , 10 , 25 ] of the 5 studies reported 2-year follow-up results. The details are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations